Kemampuan Mahasiswa Menganalisis Struktur Retorika Debat pada Mata Kuliah Menyimak Komprehensif dan Kritis - Dian Ramadan Lazuardi; Sri Murti (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2021)
This study aims to determine the ability of students to analyze the rhetorical structure of debate in Comprehensive and Critical Listening courses. The method used in this research is descriptive qualitative. The data source in this study is the result of student analysis of the 2019 presidential and vice-presidential debates. The results show that students' ability to analyze the rhetorical structure of the 2019 Presidential and Vice Presidential debates is categorized as good, with an average score of 71.18. In conclusion, students can explore the structure of the preliminary rhetoric, the content of arguments and findings from the 2019 Presidential and Vice Presidential Candidates debate. Keywords: Debate, Listening, Rhetoric Structure